A Study of the Deflections of Metal Road Guardrail Post - Olegas Prentkovskis; Andrey Beljatynskij; Edita Juodvalkienė; Rasa Prentkovskienė (The Baltic Journal of Road and Bridge Engineering)
Road guardrails of various types (made of reinforced concrete, cable and metal) are installed on the shoulders and traffic lanes of urban and suburban roads. Metal guardrails, consisting of Σ-shape and double T-shape metal posts and a protective W-shape horizontal beam, are the most popular. The deformation processes of the Σ-shape and double T-shape metal posts of the above-mentioned guardrails are examined. A mathematical model of Σ-shape (or double T-shape) metal post is developed. A metal post of Σ-shape (or double T-shape) is modeled, using one-dimensional firstorder finite elements, and taking into account elastic deformations, as well as the effect of soil on the buried post section of the guardrail. The deflections of Σ-shape and double T-shape metal posts caused by the impact of a motor vehicle moving at varying speed are determined.